О хронологических рамках кизил-кобинской (таврской) культуры - Власов, В. П. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryVlasov V. P. About Chronological Limits of Kizil-Koba CultureThe problem of the chronology of Kizil-Koba culture in Crimea is considered in this article. Researchers are not unanimous in defining the period of its existence: within time-limits of Bronze Age to early Middle Ages. Basing on the earliest dating material recently obtained (arrow-heads and fragments of bone cheek-pieces) one should date the rise of Taurian culture back to the first half of the 8th century B. C.The origin of incised decoration among Kizil-Kobians is also touched in this work. The author does not share the opinion that its beginning in the 7th century B. C. is connected with Scythians' coming to Crimea; the author thinks that Taurians inherited the principles of the ornamentation of dishes with incised decoration from the population of the epoch of Bronze and used it from the initial stage of their existence.The final date of Kizil-Koba culture is dated back to the 4th century B. C. with the help of stamped amphoras. By the above mentioned period a part of Taurians was assimilated by Scythians and Greeks and their further history, according to the written and archaeological data, continued with Late-Scythian culture.